(untitled) (Discourse of Law and Administration, 2022)
Two pre-war religious acts are still in legal circulation: the Act on the State’s Relationship to the Karaim Religious Union in the Republic of Poland of 21 April 1936, the Act on the State’s Relationship to the Muslim Religious Union in the Republic of Poland of 21 April 1936 and one Regulation of the President of the Republic of Poland of 22 March 1928 on the State’s Relationship to the Eastern Old Believers’ Church without a clerical hierarchy. The 1936 regulations were of an archaic nature, typical for the pre-war system of state authority over churches and religious associations. The provisions of both laws grant the state a number of supervisory powers over religious associations – including over the staffing of managerial positions and approval of the internal law of a religious association. These regulations are therefore incompatible with the constitutional principle of autonomy and internal independence of churches and religious associations. It must be concluded that in view of the incompatibility of the models of the relation between the state and the religious association, there is an absolute necessity to make changes to the existing particular laws of 1936. These changes must be made, according to the provisions of Article 25 paragraph 5 of the Constitution of the Republic of Poland, i.e. based on an agreement between the Council of Ministers and the relevant authorities of the religious association. The solution to these evident inconsistencies should be addressed by the legislator, as they maintain a legal state that cannot stand as a clear contradiction to constitutional principles. In this context, it is worth considering the idea of enacting a single framework religious law regulating the institutions and mutual relations of the state with the three religious associations, and highlighting the differences arising from the traditions, doctrine and specifics of each of these associations in their internal law.